The Immersive Classroom : Create Customized Learning Experiences with AR/VR - Donally, Jaime (Book collections on Project MUSE., 2021)
This book helps educators discover the possibilities of immersive technology to deepen student engagement; activate learning through hunts, breakouts and labs; and explore global collaboration.